2012
DOI: 10.1002/ccd.24366
|View full text |Cite
|
Sign up to set email alerts
|

Current operator volumes of invasive coronary procedures in medicare patients: Implications for future manpower needs in the catheterization laboratory

Abstract: There is a high percentage of low-volume operators performing PCI, raising questions regarding annual volume recommendations for procedural skill maintenance, and the future manpower requirements in the catheterization laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…36 Recognizing that 61% of PCI operators in 2008, accounting for 30% of all PCIs performed nationally, performed ≤40 Medicare fee-for-service PCIs argues for the consolidation rather than addition of cardiac catheterization laboratories and for further regionalization of PCI care. 9 Although other studies have shown an inverse relationship between hospital volume and mortality [37][38] , our study is the first meta-analysis to our knowledge to demonstrate a similar association between operator volume and outcomes.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…36 Recognizing that 61% of PCI operators in 2008, accounting for 30% of all PCIs performed nationally, performed ≤40 Medicare fee-for-service PCIs argues for the consolidation rather than addition of cardiac catheterization laboratories and for further regionalization of PCI care. 9 Although other studies have shown an inverse relationship between hospital volume and mortality [37][38] , our study is the first meta-analysis to our knowledge to demonstrate a similar association between operator volume and outcomes.…”
mentioning
confidence: 45%
“…8 The decreasing clinical requirements for coronary revascularization and the expanding availability of centers offering PCI are likely to cause average facility and operator procedural volumes to decrease dramatically in the future. 9,10 This is of particular relevance, given the adoption of minimal volume standards for competency by several major cardiovascular professional societies. 11 Decreasing average operator volumes may result in an increasing proportion of operators who fall below these minimum standards recommended for competency.…”
mentioning
confidence: 99%
“…6,16 An additional strength of our study was the comprehensive definition of periprocedural complications accounting for all major post PCIrelated complications similar to previous published analyses. 31 Over the last decade interventional cardiologists have witnessed a decline in the procedural volume 3,4 ( Figures 2 and 3). Some studies have questioned the association between operator/institutional volume and adverse outcome in the current era of technological advancements.…”
Section: Discussionmentioning
confidence: 99%
“…2 The last decade has observed a decline in number of PCIs performed, and many interventional cardiologists have experienced a drop in procedural volume. 3,4 As a result, the Background-The relationship between operator or institutional volume and outcomes among patients undergoing percutaneous coronary interventions (PCI) is unclear. Methods and Results-Cross-sectional study based on the Healthcare Cost and Utilization Project's Nationwide Inpatient Sample between 2005 to 2009.…”
mentioning
confidence: 99%
“…Indeed, a previous analysis of Medicare fee-forservice PCI data reported that a majority (≈61%) of the operators performed <40 PCIs annually. 4 We believe that administrative data sets (eg, NIS and Centers for Medicare & Medicaid Services data) complement NCDR registries. The linkage of CathPCI and other NCDR registries with longitudinal Centers for Medicare & Medicaid Services data has proven to be a quantum leap in outcomes research.…”
Section: 3mentioning
confidence: 99%